Degradation of neonicotinoid insecticide acetamiprid by two different nitrile hydratases of Pseudaminobacter salicylatoxidans CGMCC 1.17248. (February 2021) - Guo, Leilei; Yang, Wenlong; Cheng, Xi; Fan, Zhixia; Chen, Ximeng; Ge, Feng; Dai, Yijun
Abstract: Acetamiprid is a neonicotinoid insecticide used worldwide that has caused environmental pollution and adverse effects on ecosystems. Here, a novel bacterium, Pseudaminobacter salicylatoxidans CGMCC 1.17248, was isolated to rapidly degrade acetamiprid to IM-1-2 via hydration. Gene cloning and overexpression demonstrated that two nitrile hydratases, AnhA and AnhB, converted acetamiprid to IM-1-2. Escherichia coli overexpressing AnhA and AnhB degraded 98.1% and 94.0% of acetamiprid (1.0 mmol L −1 ) in 5 min and 8 h, respectively. The pure AnhA and AnhB had a V max value of 14.12 and 1.20 μmol mg −1 min −1, respectively, and a K m value of 1.02 mmol L −1 and 2.95 mmol L −1, respectively. Compared with AnhA, AnhB had broad pH stability, as well as metal ions and organic solvents tolerance. Expression of AnhA and AnhB was induced by decreasing the nutrient concentration of culture broth and addition of urea and therefore significantly enhanced acetamiprid degradation of CGMCC 1.17248. qPCR indicated that the expression of AnhA and AnhB under the cultured conditions of 1/15 lysogeny broth or 0.5% urea addition was improved by from 2.2 to 5.3 times. The results presented herein will facilitate development of bioremediation agents for acetamiprid pollution and understanding of the functional role of bacterial nitrile hydratase. Highlights: P. salicylatoxidans rapidly degraded acetamiprid in pure culture and soil. Two nitrile hydratases AnhA and AnhB converted acetamiprid to IM-1-2. AnhA and AnhB have significant differences in enzymatic properties. Nitrile hyratase genes are regulated by catabolite repression and urea induction.